The Grape Gene Reference Catalogue as a Standard Resource for Gene Selection and Genetic Improvement - Navarro-Payá, David; Santiago, Antonio; Orduña, Luis; Zhang, Chen; Amato, Alessandra; D’Inca, Erica; Fattorini, Chiara; Pezzotti, Mario; Tornielli, Giovanni Battista; Zenoni, Sara; Rustenholz, Camille; Matus, José Tomás (Frontiers in Plant Science, 2022)
Effective crop improvement, whether through selective breeding or biotech strategies, is largely dependent on the cumulative knowledge of a species’ pangenome and its containing genes. Acquiring this knowledge is specially challenging in grapevine, one of the oldest fruit crops grown worldwide, which is known to have more than 30,000 genes. Well-established research communities studying model organisms have created and maintained, through public and private funds, a diverse range of online tools and databases serving as repositories of genomes and gene function data. The lack of such resources for the non-model, but economically important, Vitis vinifera species has driven the need for a standardised collection of genes within the grapevine community. In an effort led by the Integrape COST Action CA17111, we have recently developed the first grape gene reference catalogue, where genes are ascribed to functional data, including their accession identifiers from different genome-annotation versions (https://integrape.eu/resources/genes-genomes/). We present and discuss this gene repository together with a validation-level scheme based on varied supporting evidence found in current literature. The catalogue structure and online submission form provided permits community curation. Finally, we present the Gene Cards tool, developed within the Vitis Visualization (VitViz) platform, to visualize the data collected in the catalogue and link gene function with tissue-specific expression derived from public transcriptomic data. This perspective article aims to present these resources to the community as well as highlight their potential use, in particular for plant-breeding applications.